In vitro and In vivo Trypanocidal Activity of Methanolic Extract of Lantana camara leaves on Trypanosoma brucei in Laboratory Mice - Ajaegbu Ernest Chinedu; Ezekiel Kogi (International Journal of Biochemistry and Biomolecule Research, 2024)
In this study, the methanol extract of Lantana camara leaves were tested for their trypanocidal activity in vitro in a microtiter plate and in vivo using male laboratory mice. Five different concentrations 10mg/ml, 20 mg/ml, 30 mg/ml, 40mg/ml, and 50mg/ml of the extract were prepared and the time taken to immobilize the parasites were recorded. The in vitro results showed that the leave extract at concentrations of 50 mg/ml had the most promising trypanocidal activity against Trypanosoma brucei. The LD50 value calculated from the result of the acute toxicity test was found to be 952 mg/kg. Based on this result, three different concentrations of the leave extract were prepared namely 200 mg/kg, 400mg/kg, and 800mg/kg body weight and administered to male laboratory mice in the in vivo studies. The result of the in vivo trypanocidal activity revealed that the methanol extract had no prophylactic effect against Trypanosoma brucei. However, in the curative group there was consistent parasitaemic suppression which was accompanied by prolonged time of survivals especially with treatment doses of 400mg/kg and 800mg/kg body weight daily administered intraperitoneally, even though the number of parasites were not totally wiped out within the 7 days of treatment. In the management of trypanosomiasis, the findings in this study are indicative of the trypanocidal potential of Lantana camara. Hence, we recommended that the extract of the leaves as well as other parts of this plant should be further evaluated for trypanocidal activities.
Keywords: In vitro and In vivo; Lantana Camara; Trypanosoma Brucei; methanol extract; trypanocidal activity